Photocatalytic activity of encapsulated Ag:TiO2 powder in Ag:TiO2/PVA nanofibers layers / Norizan Mohammed Lot - Mohammed Lot, Norizan (2016)
TiO2 powder is a precious photocatalyst material which is widely used as cleansing agent especially for waste water treatment Silver doping was carried out to increase the efficiency of the TiO2. For easy removal and multi-cycle used, the encapsulated Ag:TiO2 powder in Ag:TiO2/PVA nanofibers layers was successfully prepared via sol gel and electrospinning techniques by immobilize Ag doped TiO2 powder on the nanofibers and encapsulated in ‘he layers between nanofibers. The optimum concentration of Ag dopant is based on its photocatalytic activity which varied from different annealing temperature and different Ag content. All the samples were tested under UV and Solar irradiations. From the Photocatalytic result of pure TiO2 with different annealing temperature, it was found that temperature which have mixed phase of anatase and rutile was shown best performance compare to anatase m rutile phase alone. Moreover, for doping TiO2 with different Ag concentration, it was found that, 0.5wt% Ag doped TiO2 powder heated at 750°C showed to be the most effective proportion as photocatalyst with ratio of anatase to rutile is 75:25. FTIR results showed that, peak at 546cm-1 was assigned to the stretching vibration mode of Ti-O-Ti bond. After making detail analysis on FTIR band, 0.5wt% Ag doped TiO2 powder has IR band at 3410cm-1 and 1642cm-1 which capable to increase the photocatalytic activity by providing more hydroxyl radical during degradation activity. The average diameter of Ag doped is 600 nm -700 nm. The crystallite size for anatase and rutile for encapsulated Ag:TiO2 powder in Ag:TiO2/PVA nanofibers layers is 39.1nm and 61 .95nm, respectively. Encapsulated Ag:TiO2 powder in Ag:TiO2/PVA nanofibers layers succeeded to degrade the methyl orange (MO) solution within 150 minutes when expose to the UV light with kapp, value and kr, value is 33.4 x 10-3min-1 and 0.1952 mmoll-1min-1, respectively. Additionally, the performance test was conducted on the encapsulated Ag:TiO2 powder in Ag:TiO2/PVA nanofibers layers for its recycle and reuse capability. It was found then the sample can be reused to at least five complete cycles with almost consistent rate of degradation. The new finding is on the structural of the encapsulated Ag:TiO2 powder in Ag:TiO2/PVA nanofibers layers in which it can reuse for several times with consistent performance and directly give opportunity for cost saving.